Host MyD88 signaling protects against acute graft‐versus‐host disease after allogeneic bone marrow transplantation. (14th October 2018) - Xing, S.; Zhang, X.; Liu, J. H.; Huang, X.; Zhou, P.
Summary: Recent experimental strategies to reduce graft‐ versus ‐host disease (GVHD) have focused largely on modifying innate immunity. Toll‐like receptor (TLR)‐driven myeloid differentiation primary response 88 (MyD88)‐dependent signalling pathways that initiate adaptive immune function are also critical for the pathogenesis of GVHD. This study aimed to delineate the role of host MyD88 in the development of acute GVHD following fully major histocompatibility complex‐mismatched allogeneic bone marrow transplantation (BMT). When myeloablated BALB/c MyD88 knock‐out recipients were transplanted with C57BL/6 (B6) donor cells, they developed significantly more severe GVHD than wild‐type (WT) BALB/c hosts. The increased morbidity and mortality in MyD88 –/– mice correlated with increased serum levels of lipopolysaccharide and elevated inflammatory cytokines in GVHD target organs. Additionally, MyD88 deficiency in BMT recipients led to increased donor T cell expansion and more donor CD11c + cell intestinal infiltration with apoptotic cells but reduced proliferation of intestinal epithelial cells compared with that in WT BMT recipients. Decreased expression of tight junction mRNA in epithelial cells of MyD88 –/– mice suggested that MyD88 contributes to intestinal integrity. Cox‐2 expression in the GVHD‐targeted organs of WT mice is increased upon GVHD induction, but this enhanced expression was obviously inhibited by MyD88 deficiency. The present findings demonstrate an unexpected role for host MyD88 in preventing GVHD after allogeneic BMT. Abstract : Allogeneic Myd88 KO recipients developed significantly severe GvHD with increased levels of serum LPS and inflammatory cytokines, but decreased tight junction mRNA and Cox‐2 expression compared to wt recipients. MyD88 deficiency in BMT recipients led to increased donor T‐cell expansion, more donor CD11c+ cell intestinal infiltration with apoptotic cells but reduced intestinal epithelial cells proliferation compared with wt BMT recipients. Host MyD88 signaling protects against acute graft‐versus‐host disease after allogeneic bone marrow transplantation.